2011
DOI: 10.1177/0363546511417085
|View full text |Cite
|
Sign up to set email alerts
|

Single-Legged Hop Tests as Predictors of Self-Reported Knee Function in Nonoperatively Treated Individuals With Anterior Cruciate Ligament Injury

Abstract: Background Previous studies have found significant predictors for functional outcome after ACL reconstruction, however, studies examining predictors for functional outcome in non-operatively treated individuals are lacking. Hypothesis Single-legged hop tests predict self-reported knee function (IKDC2000) in non-operatively treated ACL-injured individuals 1 year after baseline testing. Study Design Cohort study (prognosis); Level of evidence, 2. Methods Ninety-one non-operatively treated subjects with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
150
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(160 citation statements)
references
References 40 publications
6
150
0
4
Order By: Relevance
“…20 The ACLR group in the current study had an average score of 72.4, which indicated that a majority were below the age-matched 15th percentile that is considered to be indicative of normal knee function. 2,19 Additionally, our ACLR group had IKDC and hop-performance scores that were below what has been reported for ACL-deficient patients 1 year after injury. 19 Recent research 3,33 has suggested that 9 months is not an adequate time for maximizing functional recovery after ACLR, which may explain the low scores in our sample and raises the possibility that further improvements may become evident at 1 year or later.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…20 The ACLR group in the current study had an average score of 72.4, which indicated that a majority were below the age-matched 15th percentile that is considered to be indicative of normal knee function. 2,19 Additionally, our ACLR group had IKDC and hop-performance scores that were below what has been reported for ACL-deficient patients 1 year after injury. 19 Recent research 3,33 has suggested that 9 months is not an adequate time for maximizing functional recovery after ACLR, which may explain the low scores in our sample and raises the possibility that further improvements may become evident at 1 year or later.…”
mentioning
confidence: 54%
“…The IKDC has been shown to be reliable, valid, and responsive in the ACL-injured population. 19 The Tegner activity scale is a measure of activity level that ranges from 0 (sick leave or disability because of knee problems) to 10 (competitive sports at national elite level).…”
Section: Self-reported Questionnairementioning
confidence: 99%
“…Several studies have found that lower extremity functional performance test results predict future functional outcome, 1,8,12,21,22 indicating their usefulness in lower extremity rehabilitation.…”
Section: 19mentioning
confidence: 99%
“…Consequently, these tests can reveal impairments in muscle force generation or proprioception and neuromuscular control that might not be obvious with other clinical measures. 7,19 Several studies have found that lower extremity functional performance test results predict future functional outcome, 1,8,12,21,22 indicating their usefulness in lower extremity rehabilitation.…”
mentioning
confidence: 99%
“…The single leg hop test for distance (SLHD) was first described by Daniel et al (1982); however, there are now a number of variations available that assess a range of functional limitations associated with ACL deficiency (Daniel et al, 1982;Daniel, Stone, Riehl, & Moore, 1988;Grindem et al, 2011;Gustavsson et al, 2006;Kramer, Nusca, Fowler, & Webster-Bogaert, 1992;Logerstedt et al, 2012). A single leg vertical jump, single leg triple hop for distance, cross over single leg hop for distance and timed six-metre single leg hop are some of the common variations (Gustavsson et al, 2006;Noyes, Barber, & Mangine, 1991).…”
Section: Single Leg Hop Testsmentioning
confidence: 99%